Implementation and Challenges of Character Education in Social Studies Learning in Elementary Schools - Puteri Melpi; Miftahul Jannah; Nurmaniah; Legi Jaya Putra Pratama; Rizki Ananda (JURNAL PENDIDIKAN IPS, 2024)
This research aims to analyze the implementation and challenges of character education in Social Sciences (IPS) learning in elementary schools. The method used is a literature study by examining various related sources obtained from various scientific articles on the Google Scholar page relating to the implementation and challenges of character education in elementary schools, especially in social studies learning. The results of the research show that the implementation of character education in school learning can be done in various ways, such as integrating character values ​​into social studies learning material, using various learning methods to develop student character, teacher example, customizing daily activities to support the character development carried out. by the school to create a positive culture and climate. However, the implementation of character education in social studies learning in elementary schools faces various challenges, such as limited teacher understanding, lack of role models from the environment, and minimal parental support. Therefore, serious efforts are needed from various parties, including schools, families and communities, to overcome these challenges and create a future generation with character.